A Pilot Study (SWOG S0429) of Weekly Cetuximab and Chest Radiotherapy for Poor-Risk Stage III Non-Small Cell Lung Cancer - Chen, Yuhchyau; Moon, James; Pandya, Kishan J.; Lau, Derick H.; Kelly, Karen; Hirsch, Fred; Gaspar, Laurie E.; Redman, Mary; Gandara, David (Frontiers in Oncology, 2013)
Purpose: Stage III non-small cell lung cancer (NSCLC) patients with poor performance status (PS) or co-morbidities are often not candidates for standard chemoradiotherapy (chemoRT) due to poor tolerance to treatments. A pilot study for poor-risk stage III NSCLC patients was conducted combining cetuximab, a chimeric monoclonal antibody targeting epidermal growth factor receptor (EGFR), with chest radiation (RT). Methods: Stage III NSCLC patients with Zubrod PS 2, or Zubrod PS 0-1 with poor pulmonary function and co-morbidities prohibiting chemoRT were eligible. A loading dose of cetuximab (400 mg/m2) was delivered week one, followed by weekly cetuximab (250 mg/m2)/RT to 64.5 Gy in 1.8 Gy daily fractions, and maintenance weekly cetuximab (250 mg/m2) for two years or until disease progression. H-score for EGFR protein expression was conducted in available tumors. Results: Twenty-four patients were enrolled. Twenty two were assessed for outcome and toxicity. Median survival was 14 months and median progression-free survival was 8 months. The response rate was 47% and disease control rate was 74%. Toxicity assessment revealed 22.7% overall ≥ Grade 3 non-hematologic toxicities. Grade 3 esophagitis was observed in one patient (5%). The skin reactions were mostly Grade 1 or 2 except two of 22 (9%) had Grade 3 acne and 1/22 (5%) had Grade 3 radiation skin burn. Grade 3-4 hypomagnesemia was seen in 4 (18%) patients. One patient (5%) had elevated cardiac troponin and pulmonary emboli. H-score did not reveal prognostic significance. An initially planned second cohort of the study did not commence due to slow accrual, which would have added weekly docetaxel to cetuximab/RT after completion of the first cohort of patients. Conclusions: Concurrent weekly cetuximab/chest RT followed by maintenance cetuximab for poor-risk stage III NSCLC was well tolerated. Further studies with larger sample sizes will be useful to establish the optimal therapeutic ratio of this regimen.